SELEKSI AMILASE PENDEGRADASI PATI MENTAH BAKTERI DARI AIR GALIAN BEKAS TAMBANG BATU BARA DI DESA LOA BAHU - Akbar Akbar; Winni Astuti; Djihan Ryn Pratiwi (JURNAL ATOMIK, 2025)
Raw starch-degrading amylase (RSDA) is a type of hydrolase enzyme that can degrade raw starch into glucose without going through the heating and gelatinization process. This study was conducted to select RSDA-producing bacteria from ex-coal mine water samples in Loa Bahu Village, Sungai Kunjang, Samarinda, with various types of raw starch such as rice, wheat, corn, potatoes, sago, and cassava. The selection of bacteria-producing RSDA enzymes was carried out using agar nutrient media containing raw starch, the positive test was marked by the formation of a clear zone around the bacterial colony after the addition of iodine solution. A total of 13 bacterial isolates (AT 1 - AT 13) were tested qualitatively by RSDA. The selection results showed that 4 bacterial isolates were capable of degrading raw rice starch, 4 bacterial isolates were capable of degrading raw corn starch, 2 bacterial isolate was capable of degrading raw cassava starch, 1 bacterial isolate was capable of degrading raw potato starch, 1 isolate was capable of degrading raw wheat starch, and 2 bacterial isolates were able to degrade raw sago starch. The bacterial isolate with the code AT3 is capable of degrading raw starch of rice, corn, potatoes, wheat and sago.